Engineering properties of concrete containing synthetic lightweight coarse aggregate using offshore sand foamed concrete (SYLCAG) - Zubir, Mohammad Amirulkhairi; Ghazali, Norhaiza; Ismail, Azlina B.H.; Muhammad Nurul Fakhri, Rusli; Mohd Hafiz Al-Kasah, Jamal Akhsah (2017)
Concrete is a material used in building construction. The concrete consisting of a hard, chemically inert particulate substance known as an aggregate (usually made from different types of sand and gravel), that is bonded together by cement and water. Aggregate is another major part of concrete besides the cement. Currently, there are many construction purposed such as house, office, shop and other building to improve the infrastructure of populations and it is caused the over-exploitation of river sand. This study, the coarse aggregates will be replaced with the synthetic lightweight coarse aggregate using offshore sand in concrete. Offshore sand is a one of alternative for river sand usage in concrete. the synthetic lightweight coarse aggregate (SYLCAG) with 1600 kg/m3 density using offshore sand. The sample of concrete placed in water tank to curing for 7 days, 14 days and 28 days. The sample was the tested with compressive strength, flexural strength and water absorption test. These tested were conducted to determine the mechanical properties of concrete using SL YCAG.